Lyric poetry and the positioning of the lyric speaker - Snarey, Nicola (2017)
Lyric poetry is frequently viewed by critics as distinct from narrative poetry and prose. This distinction rests largely on the positioning of the lyric speaker vis-à-vis the poet author. Part of any definition of the lyric is the understanding that the lyric speaker is identical to the poet and therefore the poem is the unmediated direct expression of the poet’s thoughts and experiences. These assumptions which are endemic to literary and sometimes linguistic criticism have led to restricted critical studies and a preponderance of inappropriate biographical criticism. This thesis examines how the speakers in certain types of lyric poetry are positioned, and identifies where conceptions of lyric speakers may be causing the problem of the biographical fallacy.